PURCHASE INTENTION: PERCEIVED EASE OF USE, BRAND AWARENESS DAN SOCIAL MEDIA MARKETING - Nadia Maulidya Putri (2023)
This study aims to determine, analyze and prove the effect of perceived ease of use, brand awareness and social media marketing on purchase intention. The population in this study are people who know about the Disney + Hotstar video on demand service, are over 17 years old and live in DKI Jakarta. The sample in this study were 100 people with purposive sampling method. This study uses the Partial Least Square Structural Equation Modeling (PLS-SEM) method to analyze data using SmartPLS version 4.0. The results showed that perceived ease of use has no effect on purchase intention, then brand awareness and social media marketing affect purchase intention.